2020
DOI: 10.1136/bmjmilitary-2020-001490
|View full text |Cite
|
Sign up to set email alerts
|

Killed in action (KIA): an analysis of military personnel who died of their injuries before reaching a definitive medical treatment facility in Afghanistan (2004–2014)

Abstract: IntroductionThe majority of combat deaths occur before arrival at a medical treatment facility but no previous studies have comprehensively examined this phase of care.MethodsThe UK Joint Theatre Trauma Registry was used to identify all UK military personnel who died in Afghanistan (2004–2014). These data were linked to non-medical tactical and operational records to provide an accurate timeline of events. Cause of death was determined from records taken at postmortem review. The primary objective was to repor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 22 publications
(25 reference statements)
0
13
0
2
Order By: Relevance
“…A recent review demonstrated that 57% of Armed Forces personnel killed in action in contemporary conflict died immediately and >90% died within 1 hour of wounding. 1 This review included death from head injury, and when these patients are excluded, the proportion of immediate deaths is 29.7% and the deaths within 60 min of injury was 52.1%. 1 Personal armour exists to mitigate the injurious effect of war injury and a balance must be struck between high levels of protection and the mobility and comfort of the user.…”
Section: Introduction Essential Medical Coveragementioning
confidence: 99%
“…A recent review demonstrated that 57% of Armed Forces personnel killed in action in contemporary conflict died immediately and >90% died within 1 hour of wounding. 1 This review included death from head injury, and when these patients are excluded, the proportion of immediate deaths is 29.7% and the deaths within 60 min of injury was 52.1%. 1 Personal armour exists to mitigate the injurious effect of war injury and a balance must be struck between high levels of protection and the mobility and comfort of the user.…”
Section: Introduction Essential Medical Coveragementioning
confidence: 99%
“…For this reason, we recommend that future consensus will be required about the effect extended timelines may have on the medical coverage required by personal armour. In addition, recent evidence has shown that between 2004 and 2014 during Iraq and Afghanistan, of the 448 UK Armed Forces personnel killed in action before medical treatment, 57% died immediately and 68% had died within 10 min 25. Improving survival in this cohort can only be achieved by primary or secondary prevention of tissue injury, with personal armour being a significant element.…”
Section: Future Considerationsmentioning
confidence: 99%
“…This care is delivered by personnel from a wide variety of career employment groups (CEG) as part of a system proven to be effective in saving lives 3. However, despite developments in military PHEC, the majority of combat deaths on recent operations occurred before arrival at a medical treatment facility 4. The continued innovation, development and effective employment of PHEC will be key to reducing mortality on future deployed operations 4.…”
Section: Introductionmentioning
confidence: 99%
“…However, despite developments in military PHEC, the majority of combat deaths on recent operations occurred before arrival at a medical treatment facility 4. The continued innovation, development and effective employment of PHEC will be key to reducing mortality on future deployed operations 4. In order to harness the maximum benefit of military PHEC capability, it is crucial that an operational clinical capability framework is clearly defined and understood by commanders, planners, staff officers and practitioners.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation